THROMBOPHILIA AND FAILURES OF EXTRACORPORAL FERTILIZATION - T. Y. Mashkova (IRBIS LLC, 2016)
Objective. It was study the frequency and a range of the genetic and acquired thrombophilia at patients with failures of in-vitro fertilization (IVF). Materials and methods. 115 women who had from 1 to 9 unsuccessful attempts of IVF were examined. Genetic thrombotic mutations, circulation AFA and level of a gomotsistein (an immunofermental method) were defined. Results. High frequency of the genetic forms of a thrombophilia influencing the level of an endogenous fibrinoliz (polymorphisms of plasminogen activator inhibitor-1 (PAI-1) - 66.9%, the tissue-type plasminogen activator (TPA) - 60.9%, fibrinogen - 47.8%), in combination with circulation of antiphospholipid antibodies (40.9%) is revealed. Conclusion. In the program of preparation for IVF of patients with unsuccessful attempts it is necessary to consider possible presence of the genetic and acquired thrombophilia.